2006
DOI: 10.1097/01.mlg.0000191466.09210.9a
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegrin Knockout Mice Demonstrate Abnormal Remodeling of the Otic Capsule and Progressive Hearing Loss

Abstract: The histopathological and pathophysiological findings in OPG knockout mice support the hypothesis that OPG is important in the inhibition of bone remodeling within the otic capsule and the maintenance of normal auditory function. This mouse may provide a valuable animal model of human otosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 16 publications
8
79
1
Order By: Relevance
“…We recently found that expression of OPG also best characterizes the wild-type otic capsule (unpublished data). Our previous work showed that OPG plays an important role in the inhibition of otic capsule remod-eling [Zehnder et al, 2005], and that the otic capsule of the OPG knockout mice undergoes abnormal remodeling that closely resembles otosclerosis [Zehnder et al, 2006]. Because we did not observe active remodeling in the otic capsule of Mov13 mice, it is not surprising that expression levels of OPG remained high in the Mov13 otic capsule, thus contributing to the selection of OPG as a gene that is highly characteristic of the otic capsule.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that expression of OPG also best characterizes the wild-type otic capsule (unpublished data). Our previous work showed that OPG plays an important role in the inhibition of otic capsule remod-eling [Zehnder et al, 2005], and that the otic capsule of the OPG knockout mice undergoes abnormal remodeling that closely resembles otosclerosis [Zehnder et al, 2006]. Because we did not observe active remodeling in the otic capsule of Mov13 mice, it is not surprising that expression levels of OPG remained high in the Mov13 otic capsule, thus contributing to the selection of OPG as a gene that is highly characteristic of the otic capsule.…”
Section: Discussionmentioning
confidence: 99%
“…In nonoperated persons, (35,57) Bone morphogenetic protein 4 BMP4 Role in otic capsule chondrogenesis and bone formation (58,59) Involved in the generation of inner ear sensory epithelia (60) Noggin NOG Antagonist BMPs, with high affinity for BMP2 and 4 (61) Mutations in this gene cause syndromic stapes fixation (55,56) Fibroblast growth factor 2 FGF2 Role in otic capsule chondrogenesis (62) Synergistic interaction with TGF-␤1 is required for induction otic capsule formation (62) Localized in higher concentration lining the otic capsule in the Palmerston North autoimmune mouse, which develops otic capsule sclerotic lesions (63) Osteoprotegerin TNFRSF11B Primary regulator of bone metabolism (64) Abnormal bone remodeling within the otic capsule and progressive hearing loss in knockout mice (65) Retinoic acid receptor ␣ RARA Crucial role in initial differentiation of otic placode derivatives (66) Blocking of RARA in cultured periotic mesenchyme from otocysts reduces levels of TGF-␤1 and suppresses chondrogenesis (67) Otoraplin OTOR Role in initiation of periotic mesenchym chondrogenesis (68) Parathyroid hormone PTH Key regulator in bone turnover (69) Parathyroid hormone receptor 1 PTHR1 Receptor that binds PTH and PTHLH (70) Lower expression of mRNA in otosclerotic stapes (71) Diastrophic sulfate transporter SLC26A2 Acts as a sulphate exchanger in chondrocytes (72) Mutations in this gene cause diastrophic dysplasia, a systematic skeletal disorder (73) Has a higher activity in cells from stapes and the external auditory canal of otosclerosis patients (74) POU domain class 3, transcription factor 4 POU3F4 Mutations in this gene cause DFN3, characterized by a conductive hearing loss due to fixation of the stapes and progressive sensorineural hearing loss (75) Expressed in regions of the otic capsule that immediately surround the stapes during otic development (76) Membrane co-factor protein CD46 Receptor of measles virus (77) Signaling lymphocyte activation molecule SLAMF1 Receptor of measles virus (78) (21) Genomic DNA was isolated from either fresh or frozen blood, using standard techniques.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…OTSC and PDB are among the bony disorders that can affect the otic capsule of the middle ear (Hamed & Fayad, 2009). OPG knockout mice have shown abnormal bone remodeling in the otic capsule with many similarities to OTSC in human temporal bones (Zehnder et al, 2006).…”
Section: Introductionmentioning
confidence: 99%